Pendekatan Kerangka Sampel Area untuk Estimasi dan Peramalan Produksi Padi - Mubekti Mubekti; Lena Sumargana (Perum BULOG, 2016)
The drawback of the existing national agricultural statistics system is that the acquisition of data has not been based on scientific approaches, so it results in bias of data. The aim of this paper is to introduce a new method for estimating rice area called ‘Area Frame Sampling’ based on points observation. The method employs not only statistics but also GIS, remote sensing, and information technology. Field survey to the sample points is aiming to observe and record the growth phase of rice. Data communication from field level to central level by SMS gateway is involved in supporting timely generation of reliable information on the crop area. The analysis of rice area refers to the extrapolation from sample to population, then, the estimation of rice production is a multiplication of rice harvest area and productivity derived from samples of crop cutting. Since we know both the period of growth phase and growth cycle of rice we can predict when the rice would be harvested. Each time the field survey is conducted then the acreage of each rice growth phase including harvest area can be derived. The analysis of rice area refers to the extrapolation from sample to population. Then the estimation of rice production is the multiplication of rice harvest area and productivity derived from samples of crop cutting. The accuracy of rice area estimate is good; it is indicated by the value of the coefficient of variation, namely <5 percent. It is concluded that area frame sampling approach for rice statistics can be implemented successfully and can be developed for other food crop statistics.